Fetomaternal outcome in breech delivery - Airao, Bhavesh B.; Sharma, Vishal M.; Zala, Ravi A.; Vasava, Vimal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Breech Presentation is the commonest of all malpresentations. Vaginal delivery of the breech presentations at term is associated with a much higher perinatal mortality and morbidity than that of vertex presentation. The objectives of the present study are to know the common causes leading to breech presentation. Further, to compare the different management protocols and outcome in different types of breech presentation. Also, to know the perinatal morbidity and mortality associated with different types of breech presentation nd comparison of perinatal morbidity and mortality with vaginal delivery against cesarean section. Methods: This is a retrospective study of randomized 100 cases of pregnant women in labour with breech presentations after 28 weeks or more attending C U Shah Medical College, Surendranagar, over a period of May 2012 to April 2014. Results: Out of 100 patients breech presentation was more common in booked patients and multigravida. In primi and multigravidae patients, caesarean delivery was more compared to assisted breech delivery. Perinatal outcome was good in majority of the patients in both extended and complete breech with an incidence of 94% and 88% respectively. perinatal outcome was good in caesarean section with 100% compared to assisted breech delivery 93%. Conclusions: The balanced decision about the mode of delivery on a case by case basis as well as conduct, training and regular drills of assisted breech delivery will go a long way to optimize the outcome of breech presentation like ours. Delivery of breech fetus when labor and delivery is supervised and or conducted by experienced obstetrician lowers maternal morbidity, neonatal morbidity and mortality.